2018
DOI: 10.1038/s41598-018-27567-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro-scale, mid-scale, and macro-scale in global seismicity identified by empirical mode decomposition and their multifractal characteristics

Abstract: The magnitude time-series of the global seismicity is analyzed by the empirical mode decomposition giving rise to 14 intrinsic mode functions (IMF) and a trend. Using Hurst analysis one can identify three different sums of these IMFs and the trend which exhibit distinct multifractal behaviour and correspond to micro-, mid- and macro-scales. Their multifractal detrended fluctuation analysis reveals that the micro-scale time-series exhibits anticorrelated behaviour in contrast to the mid-scale one which is long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…In this section, we present the results of ECA for the interrelation between the strong (target) EQs and the order parameter fluctuation minima β min that have been found in the regional studies of Japan [59], Eastern Mediterranean [62], and in the global seismicity [60,61], see Figure 1. For these reasons, the time-series of target EQs will serve as event time-series A and the time-series of β min as event time-series B, whereas the unit of time for ∆T and τ is one day.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, we present the results of ECA for the interrelation between the strong (target) EQs and the order parameter fluctuation minima β min that have been found in the regional studies of Japan [59], Eastern Mediterranean [62], and in the global seismicity [60,61], see Figure 1. For these reasons, the time-series of target EQs will serve as event time-series A and the time-series of β min as event time-series B, whereas the unit of time for ∆T and τ is one day.…”
Section: Resultsmentioning
confidence: 99%
“…The time evolution of β W is followed by sliding the window of W consecutive EQs, event by event, through the EQ catalog and assigning to its value the occurrence time of the EQ which follows the last EQ of the window studied in the EQ catalog. The fluctuations of the order parameter of seismicity as quantified by β W have been studied in various seismically active regions, like Japan [30,31,59] or Eastern Mediterranean [62], and in the global seismicity as well [60,61]. These studies have revealed that before strong EQs β W s exhibit characteristic minima labeled β min and were focused, so far, on a small number of the stronger EQs in each geographic region (see Tables 1-5…”
Section: Natural Time Analysismentioning
confidence: 99%
See 3 more Smart Citations